Analysis of loss probabilities on the call level and packet level in a multi-rate system - JIANG Hong-yan; LIN Ya-ping; HUANG Sheng-ye (Tongxin xuebao)
A systematic research on the performance analysis on the call level and the packet level in a system with multi-rate VBR services was made.According to the global balance condition of a multi-dimensional Markov chain,an algorithm of accurately evaluating the probability distribution of on-line connections of each service type in a system with partial sharing policy was proposed.Further,the call blocking probability and the packet loss probability were ob-tained.Simulation results show that the algorithm is accurate.